EFFECTS OF SERVICE QUALITY, HOTEL TECHNOLOGY, AND PRICE FAIRNESS ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION IN HOTEL INDUSTRY IN CAMBODIA - Prum, Sokun; Sovang, Dr. Long; Bunteng, Dr. Long (jfpublisher, 2024)
The hospitality industry plays a crucial role in contributing the country’s economy growth and, meanwhile, customer loyalty is widely regarded as important driving force for the hotel success. This study intends to discover the direct and indirect impacts of service quality, hotel technology and price fairness on customer loyalty via customer satisfaction for hotels in Cambodia. The study applies a quantitative method and conducts a non-probability survey of 500 customers accommodated in hotels located in five different selected city/provinces in Cambodia. With utilization of SPSS Amos version 23, all data are analyzed by structural equation modeling (SEM). The findings indicate that there are significantly positive relationships between service quality and price fairness on satisfaction as well as on customer loyalty, while price fairness acts as the most influencing factor and satisfaction itself has proven to be significant with customer loyalty. Furthermore, satisfaction partially mediates between service quality, price fairness and customer loyalty. However, hotel technology significantly influences on customer loyalty, yet does not on satisfaction. The research contributes to enriching the theoretical framework of customer loyalty in the hotel industry by its empirical insights. Practically, this study can assist hotel managers developing strategies for their customers retention by enhancing service quality, hotel technology and price fairness. Additionally, the government receives information from this study about the degree of customer loyalty in Cambodian hotels, which may be utilized to improve the government’s human capital training program and raise hotel performance.